Promoting dry reforming of methaneviabifunctional NiO/dolomite catalysts for production of hydrogen-rich syngas - Mohd Razali Shamsuddin; Nurul Asikin-Mijan; Tengku Sharifah Marliza; Manabu Miyamoto; Shigeyuki Uemiya; Mohd Ambar Yarmo; Yap, Taufiq Yun Hin (Royal Society of Chemistry, 2021)
Extensive effort has been focused on the advancement of an efficient catalyst for CO2 reforming of CH4 to achieve optimum catalytic activity together with cost-effectiveness and high resistance to catalyst deactivation. In this study, for the first time, a new catalytic support/catalyst system of bifunctional NiO/dolomite has been synthesized by a wet impregnation method using low-cost materials, and it shows unique performance in terms of amphoteric sites and self-reduction properties. The catalysts were loaded into a continuous micro-reactor equipped with an online GC-TCD system. The reaction was carried out with a gas mixture consisting of CH4 and CO2 in the ratio of 1 : 1 flowing 30 ml min-1 at 800 °C for 10 h. The physicochemical properties of the synthesized catalysts were determined by various methods including X-ray diffraction (XRD), N2 adsorption–desorption, H2 temperature-programmed reduction (H2-TPR), temperature-programmed desorption of CO2 (TPD-CO2), and temperature-programmed desorption of NH3 (TPD-NH3). The highest catalytic performance of the DRM reaction was shown by the 10% NiO/dolomite catalyst (CH4 & CO2 conversion, χCH4; χCO2 ~ 98% and H2 selectivity, SH2 ¼ 75%; H2/CO ~ 1 : 1 respectively). Bifunctional properties of amphoteric sites on the catalyst and self-reduction behaviour of the NiO/dolomite catalyst improved dry reforming of the CH4 process by enhancing CH4 and CO2 conversion without involving a catalyst reduction step, and the catalyst was constantly active for more than 10 h.